LIANA+ provides an all-in-one framework for cell-cell communication inference - Dimitrov, Daniel; Schäfer, Philipp; Farr, Elias; Rodriguez Mier, Pablo; Lobentanzer, Sebastian; Badia-i-Mompel, Pau; Dugourd, Aurélien; Tanevski, Jovan; Ramirez Flores, Ricardo O.; Sáez Rodríguez, Julio (Nature cell biology, 2024)
The growing availability of single-cell and spatially resolved transcriptomics has led to the development of many approaches to infer cell-cell communication, each capturing only a partial view of the complex landscape of intercellular signalling. Here we present LIANA+, a scalable framework built around a rich knowledge base to decode coordinated inter- and intracellular signalling events from single- and multi-condition datasets in both single-cell and spatially resolved data. By extending and unifying established methodologies, LIANA+ provides a comprehensive set of synergistic components to study cell-cell communication via diverse molecular mediators, including those measured in multi-omics data. LIANA+ is accessible at https://github.com/saezlab/liana-pywith extensive vignettes (https://liana-py.readthedocs.io/) and provides an all-in-one solution to intercellular communication inference.